Therapeutic Plasma Exchange in Neonatal Septic Shock: A Retrospective Cohort Study - Sawyer, Taylor; Billimoria, Zeenia; Handley, Sarah; Smith, Kendra; Yalon, Larissa; Brogan, Thomas V.; DiGeronimo, Robert (American Journal of Perinatology, 2020)
Objective This study aimed to examine the use of therapeutic plasma exchange (TPE) as adjunctive therapy in neonatal septic shock.Study Design This retrospective cohort study was performed on a convenience sample of neonates in a quaternary children's hospital between January 2018 and February 2019.Results We identified three neonates with septic shock who received TPE. Two neonates had adenovirus sepsis, and one had group B streptococcal sepsis. All neonates were on extracorporeal life support (ECLS) when TPE was started. The median duration of TPE was 6 days (interquartile range [IQR]: 3–15), with a median of four cycles (IQR: 3–5). Lactate levels decreased significantly after TPE (median before TPE: 5.4 mmol/L [IQR: 2.4–6.1] vs. median after TPE: 1.2 mmol/L [IQR: 1.0–5.8]; p < 0.001). Platelet levels did not change (median before TPE: 73,000/mm3 [IQR: 49,000–100,000] vs. median after TPE: 80,000/mm3 (IQR: 62,000–108,000); p = 0.2). Organ failure indices improved after TPE in two of the three neonates. Hypocalcemia was seen in all cases despite prophylactic calcium infusions. One neonate died, and two survived to ICU discharge.Conclusion TPE can be safely performed in neonates with septic shock. TPE may have a role as an adjunctive therapy in neonates with septic shock requiring ECLS.
Keywords: therapeutic plasma exchange; neonate; septic shock; sepsis; viral sepsis; extracorporeal life support; adenovirus; group B streptococcal sepsis